Prenatal exposure to persistent organic pollutants and childhood obesity: A systematic review and meta‐analysis of human studies. (12th November 2021) - Stratakis, Nikos; Rock, Sarah; La Merrill, Michele A.; Saez, Marc; Robinson, Oliver; Fecht, Daniela; Vrijheid, Martine; Valvi, Damaskini; Conti, David V.; McConnell, Rob; Chatzi, Vaia Lida
Summary: We conducted a systematic review and meta‐analysis of the associations between prenatal exposure to persistent organic pollutants (POPs) and childhood obesity. We focused on organochlorines (dichlorodiphenyltrichloroethane [DDT], dichlorodiphenyldichloroethylene [DDE], hexachlorobenzene [HCB], and polychlorinated biphenyls [PCBs]), perfluoroalkyl and polyfluoroalkyl substances (PFAS), and polybrominated diphenyl ethers (PBDEs) that are the POPs more widely studied in environmental birth cohorts so far. We search two databases (PubMed and Embase) through July/09/2021 and identified 33 studies reporting associations with prenatal organochlorine exposure, 21 studies reporting associations with prenatal PFAS, and five studies reporting associations with prenatal PBDEs. We conducted a qualitative review. Additionally, we performed random‐effects meta‐analyses of POP exposures, with data estimates from at least three prospective studies, and BMI‐z. Prenatal DDE and HCB levels were associated with higher BMI z ‐score in childhood (beta: 0.12, 95% CI: 0.03, 0.21; I 2 : 28.1% per study‐specific log increase of DDE and beta: 0.31, 95% CI: 0.09, 0.53; I 2 : 31.9% per study‐specific log increase of HCB). No significant associations between PCB‐153, PFOA, PFOS, or pentaPBDEs with childhood BMI were found in meta‐analyses. In individual studies, there was inconclusive evidence that POP levels were positively associated with other obesity indicators (e.g., waist circumference).